К теории цифровых измерительных устройств и их классификации - Полулях, К. С.; Тополов, Игорь Иванович (Національний науковий центр "Інститут метрології", 2017)
Представлена теория устройств цифрового преобразования, разработанная на основе принципа сравнения преобразуемой величины со ступенями образцовой меры.

The theory of digital conversion devices developed on the basis of the principle of comparing the converted quantity with the grades of the reference standard is presented in this paper.
On the theory of digital measuring devices and their classification
Keywords: математический аппарат; цифровое преобразование; образцовая мера; последовательный счет; поразрядное уравновешивание; системы счисления; разрядные коэффициенты; позиционный код; mathematical apparatus; digital conversion; reference standard; sequential count; successive approximation; numbering systems; bit factors; position code